Improvement in host metabolic homeostasis and alteration in gut microbiota in mice on the high-fat diet: A comparison of calcium supplements. (October 2020) - Cha, Kwang Hyun; Yang, Jung-Seok; Kim, Kyung-A; Yoon, Kye-Yoon; Song, Dae-Geun; Erdene-Ochir, Erdenedolgor; Kang, Kyungsu; Pan, Cheol-Ho; Ko, GwangPyo
Graphical abstract: Highlights: Ca-citrate amelorated host metabolic disorder caused by an HFD compared to Ca-carbonate. Ca supplementation altered the gut microbiota of HFD-fed mice. Ca supplementation affected microbial SCFA production. Ca-citrate affected GLP-1 gene expression and prevented metabolic endotoxemia. Abstract: Despite the previously reported health benefits of calcium intake for the attenuation of metabolic disease, few studies have investigated the relationships among calcium intake, gut microbiota, and host metabolism. In this study, we assessed the effects of calcium supplementation on host microbial community composition and metabolic homeostasis. Mice were fed a high-fat diet with different calcium concentrations (4 and 12 g/kg) of 2 calcium supplements, calcium carbonate and calcium citrate. Supplementation with the higher concentration of calcium citrate significantly prevented body weight gain and decreased plasma biomarkers for metabolic disorder compared to calcium carbonate supplementation. Both calcium supplementation led to changes in microbial composition, increased propionate production and increased anorexigenic GLP-1 gene expression. The calcium citrate groups also experienced less metabolic endotoxemia. Our findings suggested that calcium supplementation could ameliorate host metabolic disorder caused by a high-fat diet, due to gut microbiota changes as well as decreased intestinal inflammation.